Teacher Strategies in Overcoming Obstacles to Implementing Differentiated Learning at State Elementary School 206/IV, Jambi City - Siti Zulaikha; Imran Imran; Ika Panggih Wahyuningtyas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to describe teachers’ strategies in overcoming the challenges of implementing differentiated instruction at SD Negeri 206/IV Jambi City. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that teachers have implemented differentiated instruction through the adjustment of content, process, and product, as well as the use of diagnostic assessment. However, several challenges were identified, including differences in students’ abilities, limited instructional time, and difficulties in managing diverse student activities and understanding. To address these challenges, teachers applied strategies such as providing additional guidance, managing time effectively by prioritizing core learning activities, and organizing classroom activities through structured group work. This study contributes by providing a concrete description of how teachers’ strategies in addressing the challenges of differentiated instruction can be applied contextually in classroom practice, offering practical references for teachers in managing diverse learning needs and improving the effectiveness of instruction in primary education.